CARACTERIZAÇÃO DOS DANOS OCASIONADOS POR Edessa meditabunda (F.), Chinavia impicticornis (Stal) e Piezodorus guildinii (West.) (HEMIPTERA: PENTATOMIDAE) NA CULTURA DA SOJA - Husch, Patricia Elizabeth (2012)
Experiments conducted in field cages (1.0 m x 1.0 m x 1.2 m) in Ponta Grossa, Paraná, with soybean NK 3363, during the 2010/2011 season, were designed to characterize and assess the damage caused by Edessa meditabunda, Chinavia impicticornis, and Piezodorus guildinii. The plants were infested with different population levels (0, two, and three adults/m) at different phenological phases, as follows: from the beginning of grain development up to maturation (R5.1-R9); 25% to 50% of seeds filled up to maturation (R5.3-R9); completely filled seeds up to maturation (R6-R9); physiological maturity (R7-R9). Two experiments were carried out: 1) the first with the species E. meditabunda and P. guildinii and the soybean sown on November 12, 2010 and harvested on April 8, 2011 (cycle of 147 days); 2) the second with the species C. impicticornis and P. guildinii and the soybean sown on December 16, 2010 and harvested on May 2, 2011 (cycle of 150 days). The following parameters were analyzed: leaf retention; germination; yield; damage estimate with tetrazolium, classified from 1 to 8; total number of non-viable seeds. Data underwent variance analysis and the Tukey test at 5% significance level. P. guildinii caused higher leaf retention during the longest infestation period (60 days, from R5.1 to R9), with an average retention index of 4.1 (41% to 60% of the plants with symptoms of leaf retention), whereas in the shortest period of infestation (21 days, from R7 to R9), the average retention index was 3.2. The lowest germination (66.5%) was observed in plants infested at the beginning of grain development (R5.1-R9) with three adults/m of P. guildinii, as well as in plants infested at the physiological maturity (R7-R9) with three adults/m of E. meditabunda (68.7%), a species that, in the same period of infestation, caused the highest number of non-viable seeds (18.0%). C. impicticornis infestation caused the lowest percentage of germination (76.5%) during phase R5.3 with two adults/m. The highest average percentage of seeds damaged occurred with infestations during R5.1-R9, with two and three adults/m of P. guildinii, when 22.6% to 25.0% of the seeds and 63.6% to 68.0% of the seeds were damaged in the first and second experiments, respectively, in a total of 50 seeds. E. meditabunda was responsible for the greatest damage in infestations at R7, with an average of 34.0% and 41.4% of the damaged seeds in the first and second experiments, respectively. C. impicticornis affected the highest number of seeds (approximately 54.0%) in infestations with two insects/m at R6. P. guildinii caused the severe damage (36.0% of non-viable seeds) in infestations during the longest period (R5.1-R9). No significant differences were observed between the periods of infestation with two and three insects/m. The highest reduction in viability and seed vigor was caused by infestations at R5.1 with three adults/m of P. guildinii, with only 64.0% of viable seeds and 38.7% of vigorous seeds. Yield (kg ha-1) was not significantly affected between the two periods of infestation and between different population levels.